1989
DOI: 10.1007/bf01805979
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraobserver variability in the histopathological diagnosis of medullary carcinoma of the breast, and its prognostic implications

Abstract: One hundred thirty-one breast carcinomas with medullary features, registered in the Danish Breast Cancer Cooperative Group from 1977-1982, have been histopathologically reviewed by two senior pathologists and classified as typical medullary carcinoma (TMC), atypical medullary carcinoma (AMC), and non-medullary carcinoma (NMC). Diagnostic criteria were based on those put forward by Ridolfi et al. and Fisher et al. The procedure was repeated with an interval of about one year by both pathologists. The diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…Moreover, when the coassociation of individual histologic features was analyzed, the medullary subtype was most highly associated with circumscribed margins, followed by syncytial growth and lymphocytic infiltration (data not shown). These findings are similar to those of Gaffey et al 23 and contrast with Pedersen et al, 22 who found that interobserver agreement was lowest for circumscription, although the latter authors used a three-tiered scoring system for circumscription and lymphocytic infiltrate.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, when the coassociation of individual histologic features was analyzed, the medullary subtype was most highly associated with circumscribed margins, followed by syncytial growth and lymphocytic infiltration (data not shown). These findings are similar to those of Gaffey et al 23 and contrast with Pedersen et al, 22 who found that interobserver agreement was lowest for circumscription, although the latter authors used a three-tiered scoring system for circumscription and lymphocytic infiltrate.…”
Section: Discussionsupporting
confidence: 88%
“…These results are similar to that achieved by others. 21,22 In our study, the range in interobserver agreement was greatest for lymphocytic infiltrate, followed by margin status and syncytial growth pattern. Moreover, when the coassociation of individual histologic features was analyzed, the medullary subtype was most highly associated with circumscribed margins, followed by syncytial growth and lymphocytic infiltration (data not shown).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In addition, the histologic diagnosis of medullary carcinoma is fraught with interobserver variability and the disease entity is frequently overdiagnosed. [23][24][25] None of the studies that compared histopathologic observations and race mentioned the diagnostic criteria used to make the diagnosis of medullary carcinoma and most studies did not include a central pathology review.…”
Section: Medullary Carcinomamentioning
confidence: 99%
“…However there is difficulty in reproducibly making this diagnosis. [11][12][13] Also, if the Ridolfi criteria are strictly applied then less than 1% of carcinomas are of this type. 14 In addition, medullary carcinomas also share histological and immunophenotypic features with tumours that arise in carriers of BRCA1 germ-line mutations, which have a poor prognosis.…”
mentioning
confidence: 99%